The effect of extrusion conditions for a screw-disk plasticizing system on the mechanical properties of wood-polymer composites (WPC) - Michalska-Pożoga, I.; Rydzkowski, T. (Polimery, 2021)
The article presents the results of research on the impact of the disk zone conditions on the mechanical properties of wood-polymer composites. The influence of three process parameters were varied: the width of the chink of disc zone (Ws), screw speed of the screw (n) and mass participation of wood fraction (i ≤ 70 wt %). The results showed that the proper selection of conditions in the screw-disk extruder plasticizing system allowed the production of a material with better qualities.